2009
DOI: 10.1093/aje/kwp055
|View full text |Cite
|
Sign up to set email alerts
|

Using the Whole Cohort in the Analysis of Case-Cohort Data

Abstract: Case-cohort data analyses often ignore valuable information on cohort members not sampled as cases or controls. The Atherosclerosis Risk in Communities (ARIC) study investigators, for example, typically report data for just the 10%-15% of subjects sampled for substudies of their cohort of 15,972 participants. Remaining subjects contribute to stratified sampling weights only. Analysis methods implemented in the freely available R statistical system (http://cran.r-project.org/) make better use of the data throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
187
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 148 publications
(192 citation statements)
references
References 35 publications
4
187
0
1
Order By: Relevance
“…The multiple imputation estimator was compared to the standard weighted estimator [6], calibrated weights estimator [3] and re-estimated weights estimator [3]. The mean of the 1,000 log relative risk estimates, corresponding to the 1,000 subcohorts, are given in Table 6.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The multiple imputation estimator was compared to the standard weighted estimator [6], calibrated weights estimator [3] and re-estimated weights estimator [3]. The mean of the 1,000 log relative risk estimates, corresponding to the 1,000 subcohorts, are given in Table 6.…”
Section: Resultsmentioning
confidence: 99%
“…Qi et al [10] developed nonparametric methods to estimate selection probabilities and nonparametric kernel-smoothing techniques to estimate conditional expectation in fully augmented weighted estimating functions. Breslow et al [3] suggested calibrating or estimating the weights using all the phase-1 information in order to improve precision: 1) with calibration, the weights are subjected to the constraint that the cohort totals of some auxiliary variables are equal to their weighted sum among all phase-2 subjects. Practically, one builds a prediction model for the phase-2 variable to perform a simple imputation of the predicted values among the controls not belonging to the subcohort, ts the model of interest to the completed data set and uses the in uence function from the model of interest to calibrate.…”
Section: Weighted Analysis Of Case Cohort Studiesmentioning
confidence: 99%
See 3 more Smart Citations